2016
DOI: 10.4310/joc.2016.v7.n1.a7
|View full text |Cite
|
Sign up to set email alerts
|

Root-theoretic Young diagrams and Schubert calculus II

Abstract: ABSTRACT. We continue the study of root-theoretic Young diagrams (RYDs) from [SeYo13]. We provide an RYD formula for the GL n Belkale-Kumar product, after [KnPu11], and we give a translation of the indexing set of [BuKrTa09] for Schubert varieties of non-maximal isotropic Grassmannians into RYDs. We then use this translation to prove that the RYD formulas of [SeYo13] for Schubert calculus of the classical (co)adjoint varieties agree with the Pieri rules of [BuKrTa09], which were needed in the proofs of the (co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…In the companion paper [23], it is shown that our rules agree with known Pieri rules [4] (cf. [18,19]).…”
Section: Organizationsupporting
confidence: 73%
See 4 more Smart Citations
“…In the companion paper [23], it is shown that our rules agree with known Pieri rules [4] (cf. [18,19]).…”
Section: Organizationsupporting
confidence: 73%
“…The main strategy employed is to prove that the rules of Theorems 1.3 and 1.7 define an associative ring. In the companion paper [Se13+], it is shown that our rules agree with known Pieri rules [BuKrTa09] (cf. [PrRa96,PrRa03]).…”
Section: Introductionmentioning
confidence: 55%
See 3 more Smart Citations